Optimasi Campuran Carbopol 941 dan HPMC dalam Formulasi Sediaan Gel Ekstrak Daun Jambu Mete secara Simplex Lattice Design - Ilham Kuncahyo (Fakultas Farmasi Universitas Setia Budi, 2011)
Cashew leaves can be used as an antibacterial. The use of this cashew leaves in direct application can an unpractical, so it was made in the form of gel. This research was to get the gel optimum formula of the cashew leaves extract using two addition substances they were carbopol 941 and HPMC based on the simplex lattice design. The cashew leaves extract was obtained by maceration using ethanol 70% then it was evaporated to obtain concentrated extract. The optimum gel was based on simplex lattice design method with 2 components i.e. carbopol 941(C) and HPMC (H) used 3 formulations: formula I (100% C: 0% H), formula II (50% C: 50% H) and formula III (0% C: 100% H). Observation of physical properties included viscosity, the time of sticking and spreading ability, than it used to obtain SLD equation. The equation is used to make optimum gel formulation with the highest total respond of gel’s physical properties. The obtained data of simplex lattice design was compared to the result of real test by T-test. The result of the experiment showed that cashew leaves extract can be optimum formula of cashew leaves gel extract was obtained from the mixture of carbopol 941 60% - HPMC 40%. The result of t-Test of viscosity, adhesiveness and distribution showed that there was no significant difference between prediction and the result of real test.